PENYULUHAN DAN FOGGING PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) DI DESA PEKIK NYARING KECAMATAN PONDOK KELAPA BENGKULU TENGAH - Nugraheni Enny; Lestari Novriantika; Sundari Mulya; Almira Sari (DHARMA RAFLESIA, 2018)
Dengue is a transmitted disease by mosquitoes that live in the tropical and subtropical. From the available data indicate that the South East Asia has the highest number of dengue both from mild to severe. Bengkulu Province is one of the five largest endemic areas of dengue fever in Indonesia. Therefore it takes more attention and seriously handling to reduce the incidence of dengue. In order to reduce outbreaks and the spread of dengue fever transmission, then the executive team felt the need to disseminate information to the public about how to break the chain of dengue fever transmission through hygienic behaviour and keep the environment clean. In these activities, the team is also taking action to kill the vector mosquitoes which is an intermediary vector of Aedes aegypti mosquitoes by fumigation or fogging. This activity consist of two phases, the first is the counseling activites and the second is fogging. For the counseling activities folowed by all cadres in Pekik Nyaring Village as much as 33 people. The counseling activities are very interactive because some participants expressed some questions and also in these activities there are several issues that raise in every village so that it can find the solution together. All cadres in Pekik Nyaring Village have to know and understand how to breaks the transmission of dengue and prevention methods to dengue fever attacks. After this activities, it’s so expected to have more activity about preventing transmission of dengue regularly. Keywords: Counseling, DHF, fogging